2016
DOI: 10.3389/fpsyg.2016.01797
|View full text |Cite
|
Sign up to set email alerts
|

Lower Sensitivity to Happy and Angry Facial Emotions in Young Adults with Psychiatric Problems

Abstract: Many psychiatric problem domains have been associated with emotion-specific biases or general deficiencies in facial emotion identification. However, both within and between psychiatric problem domains, large variability exists in the types of emotion identification problems that were reported. Moreover, since the domain-specificity of the findings was often not addressed, it remains unclear whether patterns found for specific problem domains can be better explained by co-occurrence of other psychiatric proble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 75 publications
1
6
0
2
Order By: Relevance
“…Firstly, patients with MPD demonstrated poorer discrimination of certain emotional facial expressions relative to the HC; this was true for both angry and fearful faces presented within a neutral context, and neutral faces within a prevailing context of happy expressions. This finding both supports and extends previous research into PD: Poorer accuracy in the classification and identification of fearful faces has been reported in patients with Avoidant, Narcissistic, and Borderline PD (Rosenthal et al, 2011;Marissen et al, 2012;Semerari et al, 2014), and a lower sensitivity to anger and happiness has been observed in non-clinical individuals with avoidance problems (Vrijen et al, 2016). In MPD, this impairment in emotion processing appears to go beyond the general response bias toward negatively valenced emotions reported elsewhere (Mitchell et al, 2014;Semerari et al, 2014).…”
Section: Discussionsupporting
confidence: 88%
“…Firstly, patients with MPD demonstrated poorer discrimination of certain emotional facial expressions relative to the HC; this was true for both angry and fearful faces presented within a neutral context, and neutral faces within a prevailing context of happy expressions. This finding both supports and extends previous research into PD: Poorer accuracy in the classification and identification of fearful faces has been reported in patients with Avoidant, Narcissistic, and Borderline PD (Rosenthal et al, 2011;Marissen et al, 2012;Semerari et al, 2014), and a lower sensitivity to anger and happiness has been observed in non-clinical individuals with avoidance problems (Vrijen et al, 2016). In MPD, this impairment in emotion processing appears to go beyond the general response bias toward negatively valenced emotions reported elsewhere (Mitchell et al, 2014;Semerari et al, 2014).…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies have linked ES with higher interpersonal functioning and better quality of life (Davis, ; Mueser et al, ). Because emotion perception is reliant on complex and widespread neuropsychological processes, it can be disrupted both by psychiatric disorders such as anxiety, and by the natural aging process (Adolphs, ; Ruffman, Henry, Livingstone, & Phillips, ; Vrijen et al, ; Zhuang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Because emotion perception is reliant on complex and widespread neuropsychological processes, it can be disrupted both by psychiatric disorders such as anxiety, and by the natural aging process (Adolphs, 2002;Ruffman, Henry, Livingstone, & Phillips, 2008;Vrijen et al, 2016;Zhuang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…We used extreme bias groups rather than the full happy bias continuum because of both conceptual and methodological considerations. First and foremost, the extreme-group approach more closely fitted our supposition that mainly happy biases in the extremes of the distribution distinguish between adaptive and maladaptive affective mechanisms [29]. Second, a particular strength of network analyses is that these can be used to explore group differences in overall patterns of affect dynamics rather than investigating single effects only.…”
Section: Methodsmentioning
confidence: 73%
“…The participants had to press the spacebar as soon as they identified the emotion the neutral face turned into. For a more detailed description of the morph task, which was a shortened version of a task developed at Radboud University Nijmegen, the Netherlands [30], see Section 1 of the Supplementary Material or Vrijen et al [29]. For each participant, the mean reaction time (RT) of correctly identified trials was calculated per emotion, resulting in RT Happy, RT Sad, RT Angry, and RT Fearful.…”
Section: Methodsmentioning
confidence: 99%